PENGARUH COVID-19, VOLUME PERDAGANGAN, MARKET TO BOOK RATIO DAN KAPITALISASI PASAR TERHADAP RETURN SAHAM - Apriani, Dela; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims at how the covid-19, trading volume, market to book ratio, and market capitalization toward stock return on sector transportation, telecommunication, and mining listed on the Indonesia Stock Exchange during 2020. The sample was selected using purposive sampling method and the valid data was 140 companies. Data processing techniques using multiple regression analysis and helped by Eviews 10 program and Microsoft Excel 2013. The results of this study indicate that the covid-19, trading volume, and market capitalization have a significant influence on stock return. While market capitalization does not influence stock return. The implication of this study is the need to increase the value of trading volume and market capitalization by maintaining the quality of the company during a pandemic so that it can provide a good signal for investors.